PENGEMBANGAN PRODUK DETERGEN BIODEGRADABLE: STUDI KUALITATIF PADA PRODUK UMKM DESA MOJORANU - Romadon, Bayu; Kurniawan, Aldi; Arrochman, Refandy Ilham (Universitas Tanjungpura, 2025)
This study aims to explore the development of biodegradable detergent products based on local raw materials in Mojoranu Village through a bioentrepreneurship approach. The research investigates environmentally friendly detergent formulations using hibiscus leaves (Hibiscus tiliaceus), soapberry fruit (Sapindus rarak), and coconut oil as natural surfactant sources intended to replace synthetic chemical detergents that contribute to environmental pollution. This qualitative study involved 12 participants, consisting of local MSME actors, community members, and village stakeholders. Data were collected through in-depth interviews, direct observations, and documentation, using interview guidelines and field notes as the primary instruments. The collected data were analyzed using thematic analysis to identify patterns related to raw material potential, production processes, and socio-economic implications. The findings show that the biodegradable detergent is environmentally friendly, economically viable, and contributes to a 15% monthly income increase for local MSMEs while enhancing community empowerment. The product also aligns with sustainable development goals by reducing pollution and strengthening the local economy. However, challenges remain in product stability, shelf life, and technological refinement. The study concludes that strengthened collaboration between MSMEs, universities, and government institutions is necessary to support the long-term sustainability of biodegradable detergent innovation.